THE IMPORTANCE OF PHILOSOPHICAL METHODS AND TECHNIQUES IN SOLVING THE PROBLEM - Sattorova Yoqutxon Yax’yo Qizi; Salimov Bakhriddin Lutfullaevich (Ustozlar uchun, 2025)
In the article, laws are considered a subject of philosophy, a subject of controversy. First of all, philosophy studies the most common aspects of the relationship between mind and nature, thinking and existence, society and man, and philosophy is a science that examines the general relationship of mind to natural processes and phenomena, taking into account the development of the world, and the ways in which they are influenced. studied.